Genome-Wide Interaction and Pathway Association Studies for Body Mass Index - Jiao, Hongxiao; Zang, Yong; Zhang, Miaomiao; Zhang, Yuan; Wang, Yaogang; Wang, Kai; Price, R. Arlen; Li, Wei-Dong (Frontiers in Genetics, 2019)
Objective We investigated gene interactions (epistasis) for body mass index (BMI) in a European-American adult female cohort via genome-wide interaction analyses (GWIA) and pathway association analyses. Methods Genome-wide pairwise interaction analyses were carried out for BMI in 493 extremely obese cases (BMI>35 kg/m2) and 537 never-overweight controls (BMI<25 kg/m2). To further validate the results, specific SNPs were selected based on the GWIA results for haplotype-based association studies. Pathway-based association analyses were performed using a modified Gene Set Enrichment Algorithm (GSEA) (GenGen program) to further explore BMI-related pathways using our genome wide association study (GWAS) data set, GIANT, ENGAGE, and DIAGRAM Consortia. Results The EXOC4-1q23.1 interaction was associated with BMI, with the most significant epistasis between rs7800006 and rs10797020 (P = 2.63x10-11). In the pathway-based association analysis, Tob1 pathway showed the most significant association with BMI (empirical P<0.001, FDR= 0.044, FWER=0.040). These findings were further validated in different populations. Conclusions Genome-wide pairwise SNP-SNP interaction and pathway analyses suggest that EXOC4 and TOB1-related pathways may contribute to the development of obesity.